Fresno County Young Lawyers Association Hopper Luncheon with California Supreme Court Justice John Racanelli - Watkins, Howard::::::::: (1986)
Justice Hollis Best, Justice John Racanelli and Betty Racanelli seated and eating lunch at head table Luncheon at Golden State Plaza